The law of contract - O'Sullivan, Janet, 1967-; Hilliard, Jonathan (New York : Oxford University Press, 2010)
"The Law of Contract provides an accessible overview of the fundamentals of contract law and its underlying rationales. It also introduces and explores the main academic debates within the subject, encouraging students to decide for themselves whether the rules that contract law adopts are justifiable and, if not, how they should be altered. To help students to develop the skills necessary to apply the principles of contract law to new situations, The Law of Contract breaks down legal problems into different and manageable steps. This book covers all of the core areas studied on an undergraduate course and incorporates chapter summaries and self-test questions to reinforce students' learning and aid revision, as well as further reading sections to provide a platform for further study. Online Resource Center Updates Web links"--
General themes and issues -- Offer and acceptance I : general principles -- Offer and acceptance II : three applications of the general principles -- Certainty -- Contracts which fail to materialise -- Consideration and estoppel -- Privity -- Terms of the contract I : Terms of the contract II : exemption clauses and unfair terms -- Misrepresentations and non-disclosure -- Duress -- Undue influence -- Unconscionable bargains -- Incapacity -- Illegality and public policy -- Common mistake -- Frustration -- Discharge of a contract for breach -- Remedies I : compensatory damages -- Remedies II : specific remedies -- Remedies III : other non-compensatory remedies.
Includes bibliographical references (pages [496]-503) and index.
Keywords: Contracts -- England; Contracts -- Wales